Organic Monolayers by B(C(6)F(5))(3)-Catalyzed Siloxanation of Oxidized Silicon Surfaces - Escorihuela, Jorge (Langmuir, 2017)
[Image: see text] Inspired by the homogeneous catalyst tris(pentafluorophenyl) borane [B(C(6)F(5))(3)], which acts as a promotor of Si–H bond activation, we developed and studied a method of modifying silicon oxide surfaces using hydrosilanes with B(C(6)F(5))(3) as the catalyst. This dedihydrosiloxanation reaction yields complete surface coverage within 10 min at room temperature. Organic monolayers derived from hydrosilanes with varying carbon chain lengths (C(8)–C(18)) were prepared on oxidized Si(111) surfaces, and the thermal and hydrolytic stabilities of the obtained monolayers were investigated in acidic (pH 3) medium, basic (pH 11) medium, phosphate-buffered saline (PBS), and deionized water (neutral conditions) for up to 30 days. DFT calculations were carried out to gain insight into the mechanism, and the computational results support a mechanism involving silane activation with B(C(6)F(5))(3). This catalyzed reaction path proceeds through a low-barrier-height transition state compared to the noncatalyzed reaction path.